Analysis on microplastics in dug wells around Tamangapa Landfills, Makassar City, Indonesia - Muh. Fajaruddin Natsir; Makmur Selomo; Erniwati Ibrahim; Andi Arsunan Arsin; Nurul Chaerani Alni (Elsevier, 2021)
Objective: This study aims to determine the microplastics abundance of dug wells around Tamangapa Landfills in Makassar area. Method: The research method used is quantitative research with a descriptive. The number of samples is 8 dug wells with the criteria of 4 dug wells that are <500 m from landfills and 4 dug wells that are 500 m-1 km from landfills. Results: The most common forms of microplastics were fiber (72%) and fragments (28%). The microplastic sizes found ranged from 0.069 mm to 4.459 mm with the largest size being smaller than 2 mm (86%). The most microplastics color found was blue (53.6%). The lowest amount of microplastics content was 0.25 particles/L and the highest was 0.95 particles/L. Conclusions: This study found that the eight samples dug wells around Tamangapa landfills area were positive for microplastics and there was no relationship between the landfill distance and the dug wells on their microplastic abundance.